MicroRNA-138 regulates hypoxia-induced endothelial cell dysfunction by targeting S100A1 - Sen, Anagha; Ren, Shumei; Lerchenmüller, Carolin; Sun, Jianxin; Weiss, Norbert; Most, Patrick; Peppel, Karsten (PLOS ONE, 2013)
The Ca2+ sensor S100A1 is essential for proper endothelial cell (EC) nitric oxide (NO) synthase (eNOS) activation. S100A1 levels are greatly reduced in primary human microvascular ECs subjected to hypoxia, rendering them dysfunctional. However mechanisms that regulate S100A1 levels in ECs are unknown. Here we show that ECs transfected with a S100A1-3′ untranslated region (UTR) luciferase reporter construct display significantly reduced gene expression when subjected to low oxygen levels or chemical hypoxia. Bioinformatic analysis suggested that microRNA -138 (MiR-138) could target the 3′UTR of S100A1. Patients with critical limb ischemia (CLI) or mice subjected to femoral artery resection (FAR) displayed increased MiR-138 levels and decreased S100A1 protein expression. Consistent with this finding, hypoxia greatly increased MiR-138 levels in ECs, but not in skeletal muscle C2C12 myoblasts or differentiated myotubes or primary human vascular smooth muscle cells. Transfection of a MiR-138 mimic into ECs reduced S100A1-3 ‘UTR reporter gene expression, while transfection of an anti MiR-138 prevented the hypoxia-induced downregulation of the reporter gene. Deletion of the 22 nucleotide putative MiR-138 target site abolished the hypoxia-induced loss of reporter gene expression. Knockdown of Hif1-α mediated by siRNA prevented loss of hypoxia-induced reporter gene expression. Conversely, specific activation of Hif1-α by a selective prolyl-hydroxylase inhibitor (IOX2) reduced reporter gene expression even in the absence of hypoxia. Finally, primary ECs transfected with a MiR-138 mimic displayed reduced tube formation when plated onto Matrigel matrix and expressed less NO when stimulated with VEGF. These effects were reversed by gene transfer of S100A1 using recombinant adenovirus. We conclude that hypoxia-induced MiR-138 is an essential mediator of EC dysfunction via its ability to target the 3′UTR of S100A1.